Spatial analyticity of solutions of a nonlocal perturbation of the KdV equation - B. Alvarez Samaniego (Electronic Journal of Qualitative Theory of Differential Equations, 2005)
Let $\mathcal{H}$ denote the Hilbert transform and $η \ge 0$. We show that if the initial data of the following problems